(untitled) (The Journal of Medicine, Humanity and Media, 2025)
On July 11, 2025, MHM2025 invited Professor Li Zhenyi from Royal Roads University to deliver a summer course lecture. Titled“Social Norms Theory and Public Health Communication Research: Case Studies of Food-Related Behavioral Changes”, the lecture was both academically profound and practically valuable. Focusing on the core proposition that “the core of health communication is behavioral change”, the lecture systematically explained the application logic of social norms theory in public health communication by integrating cross-cultural empirical research, theoretical model construction and specific case analysis. It provided a new perspective for understanding the complexity of food-related behaviors and formulating effective health intervention strategies.